PERANAN SIKAP LINGKUNGAN DALAM TERBENTUKNYA NIAT BERPERILAKU HIJAU DI KALANGAN MAHASISWA UNIVERSITAS NAHDLATUL ULAMA PURWOKERTO - Prasetyo, Agung; Nugroho, Adityo (Economics, Social, and Humanities Journal (Esochum), 2024)
This research addresses the serious global environmental challenges faced by the world today, focusing on climate change caused by greenhouse gas pollution and its detrimental impacts such as flooding, disease, and environmental damage. It emphasises the need for collective efforts from all elements of society, including university students, to address this environmental crisis and build a more sustainable future. By referring to Universitas Nahdlatul Ulama Purwokerto as a case study, this research explains how Islamic principles of environmental sustainability have been integrated in education at an Islamic-based educational institution. Equipped with a literature review that investigates the theory of planned behaviour and the concept of attitude, as well as a research model that tests hypotheses about the relationship between attitude and green behavioural intention, this study shows that attitude has a significant influence on the intention to behave green. Data analysis shows that attitude variables can moderately explain green behavioural intentions, but there may be other variables that influence this process more strongly. The research conclusions highlight the importance of organisational support in strengthening the interaction between attitude and behaviour, suggesting that a deeper understanding of these dynamics could be an interesting and valuable area of research to explore further.